Síntese e Caracterização de Partículas de Óxidos de Cobalto para Detecção de Compostos Fenólicos - BONINI, JANAÍNA SARTORI (2015)
The synthesis of inorganic compounds, such as cobalt, in combination with lamellar and spinel structures, has attracted great scientific and technological interest because of relevant electrical, catalytic, and optical properties of these compounds. Using an inorganic precursor to obtain Co(OH)2, CoO(OH) e Co3O4 is simple and practical because it does not require any equipment and special conditions of preparation. This method consists of synthesizing cobalto (II) hydroxide [Co(OH)2] and subsequently obtaining its derivatives: cobalt oxyhydroxide [CoO(OH)] and cobalt tetroxide [Co3O4]. Thermal decomposition of cobalt compounds was studied by simultaneous thermal analysis (TG-DTA). Structural behavior was evaluated by X-ray diffraction (XRD), molecular spectroscopy (FTIR), and electronic spectroscopy (UV-VIS). XRD profile shows a change in the Bravais parameters, that is, there is a change in the structural organization of each one of the oxides. Vibrational and electronic spectra show the presence of di- and trivalent cobalt, as well as the effect of oxidation states on the color of the compounds. Synthesized compounds were used to determine phenolic compounds. Modified carbon paste electrodes (MCPEs) were prepared using the synthesized cobalt compounds. The following techniques were used cyclic voltammetry (CV) and linear voltammetry (LV) with experimental parameters of analytical application, such as sensors. The experimental results obtained by LV of the detection thresholds for the compounds reached satisfactory values in terms of detection of phenolic compounds, within the range of 10ˉ⁷ molLˉ¹ of the Co(OH)2 and 10ˉ⁸ mol Lˉ¹ for the derived compounds CoO(OH) e Co3O4.